PS01.093: REPEAT ESOPHAGEAL STRICTURE RESECTION: WHAT FACTORS ARE MOST INFLUENTIAL?. (14th September 2018) - Jo Svetanoff, Wendy; Bairdain, Sigrid; Zurakowski, David; Hamilton, Thomas; Smithers, C; Jennings, Russell
Abstract: Background: The objective of this study was to identify whether paralysis time following stricture resection and tension applied at the anastomosis influenced leak rate, need for repeat stricture resection (SR), or need for an interposition graft. Methods: A retrospective chart review was performed of patients undergoing esophageal stricture resection and anastomosis from October 2007 to July 2017 (IRB# P00004344). Patients who required an interposition as their primary surgery were excluded. Leak rates following stricture resection and the need for further esophageal surgery was identified. Tension groups were also delineated into mild, moderate, and high anastomotic tension. Anastomotic tension and paralysis times were analyzed by multivariable logistic regression and area under the curve (AUC) to determine factors associated with development of leaks and an increased risk of repeat SR. Results: Ninety-four patients were identified; 45 were males and mean gestational age was 35 weeks. Fifty-one patients were categorized with mild tension, 35 with moderate, and 8 with high tension. Four of the 51 patients (8%) with low tension and 15/43 (35%) with moderate or high tension developed leaks ( P = 0.002). Seventeen patients overall required repeat SR (18%), including 3/51 with low tension (6%) versus 14/43 (33%) with moderate or high tension ( P < 0.001). Additionally, 12/17 (71%) patients requiring repeat operations initially had a Foker process for their esophageal atresia. Multivariable analysis indicated that moderate/high tension ( P = 0.006) and longer paralysis time (p 0.04) were predictive of a leak after initial SR (AUC = 0.720). Paralysis time of 7 + days ( P = 0.05), moderate/high tension ( P = 0.05) and occurrence of a leak ( P = 0.002) were independent risk factors for the need for repeat SR (AUC = 0.861, 95% CI: 0.772–0.949). Of the 17 patients with repeat SR, 10 (59%) underwent a jejunal interposition. Conclusion: Tension, paralysis time, and presence of a leak are independent risk factors for repeat SR. Low tension anastomoses had a significantly small incidence of repeat surgery. Esophageal replacement shoudl be considered earlier among patients who originally undergo a Foker procedure for esophageal continuity and for those whose stricture repair is placed under moderate or high tension. Disclosure: All authors have declared no conflicts of interest.